The occurrence of black stork Ciconia nigra (L.), black grouse Tetrao tetrix (L.) and hazel hen Bonasa bonasia (L.) in Łódź region (The results of an enquiry) - Hejduk, Janusz; Markowski, Janusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
This paper presents the results of enquiry sent (in 1994) to the forest district administration in Łódź (Central Poland), concerning three forest bird species: black stork, black grouse and hazel hen. Compared to the results of older study (from 1972) the increase of black stork population is distinguishable (now about 50 breeding pairs) contrary to abruptly decreased numbers of the other two species.